Judicial diversity - Albertyn, Catherine (Juta and Co, 2014)
A judiciary controlled entirely by whites and enforcing laws enacted by a white parliament in which Africans have no representation—laws which in most cases are passed in the face of unanimous opposition from Africans— . . . cannot be regarded as an impartial tribunal in a political trial where an African stands as an accused.
Keywords: Judiary gender diversity; Fair trial; Race; Justice; Nelson Mandela